CAP reform 2014–20 : EU agreement and implementation in the UK and in Ireland /: EU agreement and implementation in the UK and in Ireland. (2013) - (Information officer), Allen, Mark; Downing, Emma; (Information officer), Edwards, Tom; Seaton, Nia; (Librarian), Semple, Maggie
No abstract available